High-Definition 4K 3D Exoscope (ORBEYETM) in Peripheral Nerve Sheath Tumor Surgery: A Preliminary, Explorative, Pilot Study. Issue 4 (1st May 2020) - Vetrano, Ignazio G; Acerbi, Francesco; Falco, Jacopo; D'Ammando, Antonio; Devigili, Grazia; Nazzi, Vittoria
Abstract: BACKGROUND: Surgery for peripheral nerve sheath tumors aims to preserve functional fascicles achieving gross-total resection. Increasing the visualization of anatomic details helps to identify the different layers and the tumor-nerve interface. The traditional microscope can present some limitations in this type of surgery, such as its physical obstruction. OBJECTIVE: To present a proof-of-concept study about exoscope-guided surgery for schwannomas of the lower limbs, to analyze the advantages and disadvantages of the 4K, high-quality, 3-dimensional (3D) imaging. METHODS: We analyzed 2 consecutive surgical cases of suspected schwannomas of the lower limbs using the ORBEYE™ exoscope (Olympus). A standard operative microscope was also available in the operating room. All procedures were performed with neurophysiological monitoring, to identify functioning nerves and to localize the tumor capsule safest entry point. The cases are reported according to the PROCESS guidelines. RESULTS: In both cases, we achieved a gross total resection of the schwannomas; the exoscope provided an excellent view of the anatomic details at tumor-nerve interface, as visible in intraoperative images and in the 3D-4K video supporting these findings. The surgeon's position was comfortable in both cases, although if the co-surgeon positioned himself in front of the first surgeon, the comfort was slightly reduced. The 4K monitor allowed a realistic, nontiring 3D vision for all the team. CONCLUSION: The ORBEYE TM, after an adequate learning curve, can represent a feasible and comfortable instrument for nerve tumor surgery, which is usually performed in a single horizontal plane. Further and wider clinical series are necessary to confirm this first impression.